Strategi Bisnis Kuliner Aceh: Transformasi Identitas Islami Melalui Inovasi Dan Komodifikasi - agustinar, Agustinar; Sumarni, Mutia; Mufida, Laila (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2023)
Abstract The aim of this research is to examine Aceh's culinary business strategy which emphasizes commodification and innovation in order to transform Islamic identity. Aceh's rich culinary heritage reflects the varied and diverse Islamic values that make it the home of Mecca. This study looks at how innovative menus, presentation and customer experience are used by Acehnese food companies to project a strong Islamic identity. This research methodology is qualitative with a descriptive analysis approach including direct observation of industrial operations, literature review, interviews with industry professionals in the culinary arts field, and documentation. The findings of this research show how creative culinary entrepreneurs in Aceh are actively implementing new ideas in preparing and serving food in a way that respects Islamic principles. In addition, the use of branding, MPU Aceh's halal certification, and the provision of places of worship all contribute to the commodification of Islamic identity and are important components of business strategy. The results of this research are that this change in Islamic identity is increasing the gastronomic appeal of Aceh, both among local people and visitors. This business plan is expected to uphold and preserve Aceh's Islamic culinary heritage and have a positive impact on regional economic growth. These results provide in-depth information for the growth of culinary businesses based on Islamic identity in a similar context. Keywords: Commodification of Identity, Business Strategy, Acehnese Culinary